Role of sports activities in developing the important life skill of decision making; a psychological perspective - Wasim Khan; Salahuddin Khan; Tasleem Arif; Sohail Roman Khan (Physical Education of Students)
Purpose:It is generally believed that sports can play an important role in developing life skills and positive youth development. The purpose of this study was to determine the views of Gomal University students’ athletes on the role that sports played in developing the important life skill of decision making. The time management, planning, dealing with adversity and adapting new situation were taken as decision-making skills. Materials:A sample of n=375 (male=334, female=41 completed questionnaires. The researchers collected the required information with the help of self-administered structured questionnaire encompassing the selected variables of the study. The responses were tabulated and analyzed with the help of computer software. Results:The results showed participants attributed a significant role for sports in developing decision-making skills such as time management, planning, dealing with adversity and adapting new situation (603** at 0.01) and significant correlation between sports participation and the development of various decision-making skills among its participants (603** at 0.01). The results indicated that demographic characteristic such as gender, age, and level of sports participation of the athletes brings variations in the mean score of research variables (0.003, 0.004 & 0.001 < 0.05). conclusions:Results of the study indicated that sports provide an excellent opportunity for students to learn skills that can help them in taking positive as well as effective decision. The present exploration affirmed that students can acquire a) time management skill, b) proper planning, c) dealing with adversity, and d) the ability to adjust in a new situation through active participation in sports activities. However, some demographic characteristics of the sports participants such as gender, sports experience, and format of sports have an influence upon the development of these skills through sports.